Effect of the frying process on the composition of hydroxycinnamic acid derivatives and antioxidant activity in flesh colored potatoes. (1st December 2018) - Ruiz, Antonieta; Aguilera, Ariel; Ercoli, Stefano; Parada, José; Winterhalter, Peter; Contreras, Boris; Cornejo, Pablo
Highlights: Frying increases hydroxycinnamic acid concentrations in pigmented potatoes. There is a correlation between hydroxycinnamic acid concentration and antioxidant activity. Hydroxycinnamic acids are the most abundant phenolic compounds in fried potatoes. Abstract: Phenolic composition of potatoes ( Solanum tuberosum ) with colored flesh has been previously reported, highlighting their anthocyanin composition. However, there is less information available about the profiles and concentrations of hydroxycinnamic acid derivatives (HCADs) in these potatoes. In pigmented potatoes from Southern Chile, three HCADs have been detected, corresponding to the trans isomers of 3-, 4- and 5-caffeoylquinic acid. It is remarkable that after frying, the HCAD concentrations increased 493% compared to those of fresh potatoes. The same tendency has been observed for total phenols and antioxidant activity of the chips. The results obtained are relevant in relation to the classification of pigmented potatoes as functional foods not only due to their anthocyanin content but also due to their higher content of HCADs, especially since their concentration increases considerably after frying, thus contributing to their antioxidant activity and potential beneficial effects for human health compared with uncolored genotypes.